External application of nitrogen alleviates toxicity of cadmium on poplars via starch and sucrose metabolism. (7th May 2021) - He, Fang; Zhao, Qian; Huang, Jin-Liang; Niu, Meng-Xue; Feng, Hua-Cong; Shi, Yu-Jie; Zhao, Kuang-Ji; Cui, Xing-Lei; Wu, Xiao-Lu; Mi, Jia-Xuan; Zhong, Yu; Liu, Qing-Lin; et al.
Abstract: Phytoremediation technology can help achieve moderate cost and considerable effect with respect to the remediation of heavy metal (HM) pollution in soil and water. Many previous studies have suggested the role of nitrogen (N) in the alleviation of effects of HM on plants. Herein, we sought to determine the molecular mechanisms by which additional N supplementation mitigates cadmium (Cd) toxicity in poplars using a combination of physiological, transcriptomic and phosphoproteomic analyses. The application of N can alleviate the toxicity of Cd to Populus by reducing chlorophyll degradation, maintaining the stability of ions inside and outside the cell membrane and increasing the soluble sugar content. Plant samples from the control, Cd stress and Cd_N treatments were used for an integrated analysis of the transcriptome, as well as for phosphoproteomics analysis. Moreover, 1314 differentially expressed genes and 119 differentially expressed kinase genes were discovered. Application of additional N under Cd stress promoted the phosphorylation process. Furthermore, 51 significantly enriched phosphorylated protein sites and 23 differentially expressed kinases were identified using phosphoproteomic and proteomic analyses. Importantly, transcriptomic and phosphoproteomic analyses jointly determined that the application of N could activate corresponding gene expression [ UDP-glucose-dehydrogenase ( UGD ), GAUT, PME, pectin lyase, UDP-glucose-pyrophosphorylase 2 ( UGP2 ), sucrose phosphate synthase ( SPS ), SUS and SPP2 ] and protein phosphorylation ( UGP2 and SPS ) in the sugar and starch synthesis pathways, which promoted the synthesis of sucrose and soluble sugar and subsequently alleviated the damage caused by Cd.